Exploring non-communicable disease prevalence and risk factors among construction workers in urban Mysuru - P. V., Manirsha; Shruddha; D., Sunil Kumar; Gopi, Arun (International Journal Of Community Medicine And Public Health, 2025)
Background: Non-communicable diseases (NCDs), including hypertension, diabetes, which constitutes major contribution to global morbidity and mortality. While lifestyle factors are well-documented contributors, the occupational exposures also play a crucial role. Construction workers, particularly in India’s unorganized sector, face multiple risk factors such as physically demanding labour, hazardous work environments, and limited healthcare access. This study aimed to assess the prevalence and risk factors of NCDs among construction workers in urban Mysuru. Methods: A cross-sectional study was conducted among 125 male construction workers aged 18 years and above over two months (October-November 2024). Data were collected using a semi-structured questionnaire, and health assessments included body mass index (BMI), waist-hip ratio (WHR), blood pressure (BP), and random blood sugar (RBS). Statistical analysis was performed using SPSS version 30, with logistic regression to determine associations between socio-demographic variables and NCD risk factors. Results: Hypertension prevalence was 32.8%, significantly associated with age (p<0.001) and tobacco use (p=0.026). Diabetes prevalence was 13.7%, also significantly associated with age (p<0.001) and tobacco use (p=0.001). Unexpectedly, non-smokers had significantly higher odds of diabetes (AOR: 13.146, p=0.012). The most commonly reported health complaints were myalgia (32.8%), general weakness (18.4%), and skin infections (11.2%). Conclusions: Construction workers in Mysuru exhibit a substantial burden of NCDs, with age and tobacco use as significant risk factors. Targeted interventions, including workplace health programs and preventive screenings, are essential to mitigate these risks and improve worker well-being.